The Application of Case Teaching Method in the Ideological and Political Construction of College Courses - Yang, Tuo (Journal of Theory and Practice of Social Science, 2023)
Curriculum ideological and political construction is a major practice to enhance the comprehensive quality of students in ordinary colleges and universities. The integration of ideological, political and moral education elements into professional courses embodies the teaching goal of "cultivating morality and cultivating people". The tax law course is the core compulsory course for economic management majors. It contains many ideological and political elements. Through the case teaching method, the content of ideological and political education and professional knowledge points are organically integrated to cultivate and enhance students' awareness of the rule of law, public awareness and social responsibility. As an important method for the ideological and political construction of tax law courses, the case teaching method is also expected to play an exemplary role in other economic management courses.